2010
DOI: 10.1016/j.cell.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporins Directly Stimulate Expression of Developmental and Cell-Cycle Genes Inside the Nucleoplasm

Abstract: Nuclear pore complexes (NPCs) mediate transport across the nuclear envelope. In yeast, they also interact with active genes, attracting or retaining them at the nuclear periphery. In higher eukaryotes, some NPC components (nucleoporins) are also found in the nucleoplasm, with a so far unknown function. We have functionally characterized nucleoporin-chromatin interactions specifically at the NPC or within the nucleoplasm in Drosophila. We analyzed genomic interactions of full-length nucleoporins Nup98, Nup50, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
429
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 404 publications
(456 citation statements)
references
References 60 publications
(87 reference statements)
24
429
2
1
Order By: Relevance
“…Studies have shown that Nup98 localizes predominantly to the nuclear pore complex, but has an additional population in the nucleoplasm and can exhibit altered nuclear distribution in response to some stimuli, such as developmental signaling or IFN-γ (19,20,22,34). In our system, we found that Nup98 levels are increased on viral infection (Fig.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Studies have shown that Nup98 localizes predominantly to the nuclear pore complex, but has an additional population in the nucleoplasm and can exhibit altered nuclear distribution in response to some stimuli, such as developmental signaling or IFN-γ (19,20,22,34). In our system, we found that Nup98 levels are increased on viral infection (Fig.…”
Section: Resultssupporting
confidence: 65%
“…The classically described role for Nups is within the nuclear pore complex, with specific functions in the transport of macromolecules in and out of the nucleus (37-39); however, recent studies have found both on-pore and off-pore roles for a subset of Nups (19,20). Using two independent assays, we found no defect in nuclear export or import on depletion of Nup98 or several other nuclear pore proteins.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations